Rock Failure Assessment on Paleo-Collapse in Case of the Prasat Hin Pan Yod tourist site, Satun Geopark, Thailand - Khundee, Sakda; Kukham, Sarinthip; Uthairat, Saowaphap; Kererattanasathian, Visuttipong; Tima, Kittikorn; Rakhangkul, Tanawat (Thai Geoscience Journal, 2023)
Rockfall and rockslide incidents are currently severe geohazards affecting marine tourism in Thailand. Lately, some tourist sites, located both in the Gulf of Thailand and the Andaman Sea, were prohibited to access. Prasat Hin Pan Yod, the study area developed from a paleo-collapse sinkhole on Khao Yai Island of Satun province, is now confronting unsafe caused by rockfall and rockslide hazards as well. The study applied the integration of simple multi-criteria in GIS, traditional stereographic projection analysis, and Slope Mass Rating (SMR) to determine the rock mass instability of limestones and to find a safe route entrancing the Prasat Hin Pan Yod tourist site. Various discontinuities on the outcrop slopes relating to geomorphological features such as sea cliff, sea cave, and a former broken block of the rockslide were investigated and assessed the rock mass stability. The study result shows that the dominant wedge failure of rockfall can occur in many spots of the Prasat Hin Pan Yod tourist site. Small pieces of broken limestone hanging on high spots and also filling in rock niches are often found during the field investigation. Rock fragments splitting off the rock face may fall away whenever it is triggered by heavy rain or ground shaking. Direct toppling failure is the comparative subordinate of the rockfall hazard. Its negative impact is similar to wedge failure and difficult to perform risk management as well. Planar failure and toppling failure seem to be low scores and rarely occur the two big severe events happened from that failure modes and revealed obvious field evidence of broken blocks. The precedent event was caused by toppling failure and the latest, February 20, 2021, was originated by planar failure. The previous route getting through the Prasat Hin Pan Yod chamber is not suitable now. Depending on the high SMR score and a few joint intersections causing the geohazard, a narrow strait located between the former broken block and sea cliff is determined as the new safe route for tourists. Moreover, Kayaks should be adopted to use for moving through the narrow strait and permitted for in and out. The tourist numbers visiting the site should be controlled. A Helmet is suggested for more safety as it can protect the tourists from the hanging rock falling from high places.